The Effectiveness of English British Council Application on Second Semester Students’ Reading Skill at Universitas Bhinneka PGRI In Academic Year 2023/2024 - Aruna Wisnu Ardana; Ika Rakhmawati (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2024)
This study aims to assess the effectiveness of the English British Council in improving the English reading skills of second semester students at Bhinneka PGRI University in the academic year 2023/2024. The experimental method was conducted at the university, focusing on second semester students during that academic year, with a sample of 22 students. The results showed a significant improvement in reading skills after using the British Council English application in learning. The difference in scores between the pre-test (63.41) and post-test (89.55) showed the success of the app. The paired samples t-test confirmed the results with a significance of 0.000, indicating the rejection of the null hypothesis in favor of the alternative hypothesis. In conclusion, the use of English British Council is effective in improving students' English reading skills